2014
DOI: 10.3390/rs6109412
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Penetration Bias of ENVISAT Altimeter Observations over Antarctica in Comparison to ICESat Observations

Abstract: Abstract:The aim of this article is to characterize the penetration bias of the ENVIronmental SATellite (ENVISAT) radar altimeter over the Antarctic ice sheet through comparison with the more accurate measurements of the Ice, Cloud and land Elevation Satellite (ICESat) altimeter at crossover points. We studied the difference between ENVISAT and ICESat fluctuations over six years. We observed the same patterns between the leading edge width and the elevation difference. Both parameters are linked, and the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Wingham et al (1998), Davis and Ferguson (2004), McMillan et al (2014) and Zwally et al (2015) apply a linear regression using the backscattered power. Flament and Rémy (2012), Michel et al (2014) and Simonsen and Sørensen (2017) use two additional waveform shape parameters, obtained from functional fit retrackers. Nilsson et al (2016) showed that a low threshold retracker mitigates the need for a complex waveform shape correction.…”
Section: Repeat-track Parameter Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Wingham et al (1998), Davis and Ferguson (2004), McMillan et al (2014) and Zwally et al (2015) apply a linear regression using the backscattered power. Flament and Rémy (2012), Michel et al (2014) and Simonsen and Sørensen (2017) use two additional waveform shape parameters, obtained from functional fit retrackers. Nilsson et al (2016) showed that a low threshold retracker mitigates the need for a complex waveform shape correction.…”
Section: Repeat-track Parameter Fitmentioning
confidence: 99%
“…Rignot (2006) showed that the flow velocity of these glaciers, which are www.the-cryosphere.net/13/427/2019/ The Cryosphere, 13, 427-449, 2019 grounded well below sea level, was above the balance velocity for many years. Miles et al (2018) analyzed satellite images since 1973 and found that the flow velocity of Cook Ice Shelf glaciers has significantly accelerated since then. In contrast, the western sector of the EAIS (Coats Land, Dronning Maud Land and Enderby Land; basins J"-B) shows thickening over the last 25 years at rates of up to a decimeter per year.…”
Section: Surface Elevation Changesmentioning
confidence: 99%
“…However, altimetric observations are affected by several errors: error due to atmospheric or ionospheric propagations, slope error and error due to the radar wave penetration into the cold and dry snow (Ridley and Partington, 1988). The first two errors are usually corrected with good accuracy (Remy et al, 2012;Nilsson et al, 2016), while the last one is the most critical and the most challenging problem to tackle (Remy et al, 2012) as it results in an overestimation of the observed distance between the satellite and the target, leading to a negative bias in the surface elevation estimation. The magnitude of the penetration error on the estimated surface elevation is between a few tens of centimeters and few meters (Remy and Parouty, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the penetration error on the estimated surface elevation is between a few tens of centimeters and few meters (Remy and Parouty, 2009). For instance, Michel et al (2014) have found a surface elevation difference of −0.5 m between ENVIronment SATellite (EN-VISAT) and ICESat crossover points over Antarctica. Authors relate this negative bias to the difference in the penetration depth between the radar altimeter wave that penetrates within the snowpack and the laser altimeter beam that does not penetrate within the snowpack.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1991, Greenland and Antarctica to 81.5°south had been covered continuously by the European Space Agency (ESA) radar altimeters on the European Remote Sensing Satellites (Fé mé nias, P. et al, 1993;Anita C. Brenner et al, 2007; Auré lie Michel et al, 2014). The ENVISAT was launched in 2002 by the ESA to link up with ERS-1 and ERS-2.…”
Section: Introductionmentioning
confidence: 99%